Limb body wall complex – the history of the entity and presentation of our series of cases - Gulczyński, Jacek; Świątkowska-Freund, Małgorzata; Paluchowski, Piotr; Hermann-Okoniewska, Blanka; Iżycka-Świeszewska, Ewa (Polish Journal of Pathology, 2019)
We present an analysis of two first historically documented limb body wall complex (LBWC) cases and our own contemporary perinatal autopsy series of this rare complex. So far it was supposed that the first case of this complex was reported in 1685 by Paul Portal. Studying the Joachim Oelhaf’s autopsy report from 1613 with attached engraving showing the neonate with multiple birth defects led our research team to a conclusion that it was genuinely the first description of LBWC in the medical literature so far. We compared the Oelhaf’s case from 1613 and the Portal’s autopsy report from 1685 with our series of LBWC cases dissected in the Medical University of Gdansk between 1999 and 2011. Reviewing 1100 autopsy reports performed we encountered 9 cases of this unique complex. The analysis was supported by the literature review.